Systematic literature review of humanistic and economic burdens of chronic rhinosinusitis with nasal polyposis. (1st November 2020) - Chen, Stephanie; Zhou, Anna; Emmanuel, Benjamin; Garcia, David; Rosta, Emily
Abstract: Objectives: We conducted a systematic literature review (SLR) of randomized controlled trials and real-world evidence (RWE) studies to determine the humanistic (e.g. health-related/disease-specific quality of life [QOL]) and economic (e.g. direct and indirect costs) burdens of chronic rhinosinusitis with nasal polyposis (CRSwNP). Methods: The SLR adhered to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Embase, MEDLINE and Evidence-Based Medicine Reviews databases were searched using OVID. Relevant studies involving adult patients with CRSwNP published between 1 January 2008 and 16 February 2019 were included, with relevant conference abstracts from 1 January 2017, onward. Results: Sino-Nasal Outcomes Test (SNOT)-22 was the most frequently used disease-specific health-related QOL/patient-reported outcomes instrument for patients with CRSwNP. Baseline SNOT-22 scores ranged from 25 to 73 for surgical candidates and from 14 to 56 for medically managed patients with CRSwNP. Mean baseline EuroQol-5 Dimensions (EQ-5D) index for patients with CRSwNP ranged from 0.81 to 0.86, and mean baseline Short Form-6 Dimensions (SF-6D) ranged from 0.67 to 0.75. Three months (EQ-5D) and 5 years (SF-6D) post-endoscopic sinus surgery (ESS), rates increased from 0.81 to 0.89 and from 0.69 to 0.80, respectively. One year post-diagnosis, patients with CRSwNP had significantly more systemic prescriptions, underwent significantly more medical procedures, demonstrated greater health care resource utilization and had significantly greater mean health care costs compared with matched controls (all p  < .001). Overall, for patients with initial ESS, CRSwNP was associated with higher disease-related expenditures compared with CRS without nasal polyposis (NP), even for patients who did not undergo revision surgery. Conclusions: This SLR identified substantial humanistic burden among surgery candidates. RWE shows that surgeries were used to treat relatively more severe CRSwNP patients as recommended by guidelines. Patient QOL is improved significantly after surgery; however, there is a lack of evidence on patients with revision surgery. Surgery is also associated with higher costs, and the presence of NP was a predictor of revision surgery. Patients with CRSwNP demonstrate greater health care resource utilization and costs compared to those with CRS without NP. Costs associated with different severity of CRSwNP and revision surgery need to be assessed further.